Usage statistics for decision making - Bucknell, Terry; Taylor-Roe, Jill; Killick, Selena A.; Thompson, Sarah (Cranfield University, 2014)
Libraries have access to more data than ever before about the way that their electronic resources are being used by readers, and advances in standardization led by the COUNTER initiative are making these more accessible and reliable as a basis for decision making. At the same time, public sector institutions are being asked to make extremely difficult choices about priorities for spending. Responding to these concerns, UKSG hosted a new seminar in November 2010 in the stately London setting of the Institute of Materials, Minerals and Mining offering a number of case studies to demonstrate how usage statistics are informing the decision-making process in real life, and highlighting some of the perils and pitfalls of taking them at face value. The Editors of Serials thought that it would be useful to provide brief summaries of the papers presented for those who were unable to attend.